Medieval Paradigms: Volume II
XVI, 293 p.
Keywords: This collection of essays in two volumes explores patterns of medieval society and culture, spanning from the close of the late antique period to the beginnings of the Renaissance. Volume 2 analyzes of forms of devotion, both popular movements and those practices and ceremonies limited to elite groups. The exploration of medieval paradigms comes to a close with a group of essays which follow the medieval patterns well past the Middle Ages, even into the present.